If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5=(2-7n)
We move all terms to the left:
5-((2-7n))=0
We add all the numbers together, and all the variables
-((-7n+2))+5=0
We calculate terms in parentheses: -((-7n+2)), so:We get rid of parentheses
(-7n+2)
We get rid of parentheses
-7n+2
Back to the equation:
-(-7n+2)
7n-2+5=0
We add all the numbers together, and all the variables
7n+3=0
We move all terms containing n to the left, all other terms to the right
7n=-3
n=-3/7
n=-3/7
| 2x(7-1)+15+5=110+6x | | n/8=12,n= | | 3x+15=x+15=4x-10 | | 6-3x=5x | | -x2+7x-100=0 | | m/7=3,m= | | 5t-4t-t+3t=15 | | 11s=88,s= | | 18g-1=15+17g | | –3n=–4−2n | | 5/f+7=-3 | | 4x-2+8=12 | | 3n+20-n=10 | | 100+50+2x=180 | | 20w+3w-6w+3w-19w=19 | | 3y+4y=26-12 | | X^2+3x+24=12 | | 0.75(8=e)=2-1.25 | | 9/w=25/100 | | 5(x-1)1=2x+4(x-1) | | -4(w+1)=(-24) | | 11x^2-16=-16x+6x^2 | | (9(x+2)-6)=19x | | 4. 3000–x=999 | | 3x+48+(x+32)=180 | | 13z-13z+5z=10 | | 6x/18=81 | | -4(3g-2)+g=18-2(g+8) | | 2y+2y=63 | | 2x3=x+13 | | -4=17(3)+b | | 4-9h=-68 |